2015
DOI: 10.4103/2229-5178.156391
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine in autologous serum skin test positive chronic urticaria: A case-control study in a tertiary care hospital of eastern India

Abstract: Context:Urticaria, also referred to as hives or wheals is a common and distinctive reaction pattern characterized by spontaneous eruption of wheals. About 30–50% of patients categorized as idiopathic urticaria have autoimmune urticaria, needing immunosuppressive agents. Immunosuppressive agents are either too costly or have serious side effects. Azathioprine seems to address both these issues, being less costly.Aims:The aim was to evaluate the role of azathioprine in autologous serum skin test (ASST) positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In the present study, adequate monitoring was routinely performed, and both agents were found to be safe, and serious adverse effects warranting the discontinuation of treatment were not noticed. This can be attributed to low doses of cyclosporine and azathioprine employed (comparable to prior study on azathioprine 8 ). Both agents rendered antihistamine-resistant disease adequately responsive to antihistamines for the intended study duration and scored comparably on global patient satisfaction score at the end of the study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the present study, adequate monitoring was routinely performed, and both agents were found to be safe, and serious adverse effects warranting the discontinuation of treatment were not noticed. This can be attributed to low doses of cyclosporine and azathioprine employed (comparable to prior study on azathioprine 8 ). Both agents rendered antihistamine-resistant disease adequately responsive to antihistamines for the intended study duration and scored comparably on global patient satisfaction score at the end of the study.…”
Section: Discussionsupporting
confidence: 74%
“…There are only 2 prior publications stating the efficacy of azathioprine in CU. A placebo-controlled study by Bhanja et al., 8 found low-dose azathioprine (50 ​mg/day) to be effective in a cohort of ASST positive CSU patients and the remission lasted till 36 weeks. Azathioprine was also employed successfully in 2 patients having resistant urticaria who had failed high-dose cyclosporine 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 14 records met the inclusion criteria and were included in the NMA ( Figure 1 ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Detailed information on all studies included in the NMA is presented in Table 1 , and Table S2 shows information of studies excluded from the NMA [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Treatments that were eligible for the evidence network were cyclosporin, methotrexate, hydroxychloroquine, omalizumab, and montelukast. We excluded the trials with azathioprine due to insufficient outcome evaluations and no placebo comparator [ 31 , 32 ]. Based on the overall risk-of-bias assessment, 12 trials had a low risk of bias, 2 trials had some concerns, and no trials had a high risk of bias ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%